Concentration Response and Frequency of Biomi Liquid Organic Fertilizer Application for the Growth and Yield of Young Okra Plants (Abelmoschus esculentus L.) - Kadek Satriawan; Made Sri Yuliartini; Luh Kartini (Warmadewa University Press, 2019)
The study aims to determine the concentration and the appropriate frequency of biomi liquid organic fertilizer application for the growth and yield of okra plants. This experiment was a factorial experiment designed using a Randomized-group Design, which consisted of two treatments, comprising the concentration of liquid organic biomi fertilizer (C) and frequency of application (F). The results of the data analysis showed that the concentration of liquid organic fertilizer biomi (C) had a significant effect (P